Excellence and efficiency in the delivery system at pre-university level - Row, Kingsley * (Sunway University College, 2010)
In the current educational climate in Malaysia, the very relevance of pre-university programmes of study is increasingly being questioned. As such, a concerted drive by pre-university educators towards excellence and efficacy is vital if such programmes are to resist the eventual slide into oblivion. This paper aims to take a critical look at the delivery system. It identifies and discusses some inherent weaknesses in the system and emphasizes the role of the educator in shaping an environment that is conducive to effective learning whilst taking cognizance of the numerous factors outside the orbit of the educator that can compromise the effectual delivery of subject matter. The paper also makes recommendations towards the attainment of excellence and efficacy in the delivery system, drawing conclusions from a survey conducted amongst past and present students as well as actual classroom experience. These recommendations are based on personal opinions and broad pedagogical philosophies rather than on actual teaching methodologies.